2013
DOI: 10.5625/lar.2013.29.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of neural stem cells for treating various human neurological diseases in animal models

Abstract: Stem cells derived from adult tissues or the inner cell mass (ICM) of embryos in the mammalian blastocyst (BL) stage are capable of self-renewal and have remarkable potential for undergoing lineage-specific differentiation under in vitro culturing conditions. In particular, neural stem cells (NSCs) that self-renew and differentiate into major cell types of the brain exist in the developing and adult central nervous system (CNS). The exact function and distribution of NSCs has been assessed, and they represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 68 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…Neural stem/precursor cells (NSCs) are multipotent cells, capable of differentiating into the main phenotypes of the central nervous system, namely neurons, astrocytes and oligodendrocytes (Yi et al, 2013). NSCs can be isolated from developing or adult central nervous system tissue (Bennett et al, 2009;Meyer et al, 2010) and cultured in vitro as free-floating spheres (neurospheres) in the presence of endothelium growth factor and/or basic fibroblast growth factor (Bonnamain et al, 2012).…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…Neural stem/precursor cells (NSCs) are multipotent cells, capable of differentiating into the main phenotypes of the central nervous system, namely neurons, astrocytes and oligodendrocytes (Yi et al, 2013). NSCs can be isolated from developing or adult central nervous system tissue (Bennett et al, 2009;Meyer et al, 2010) and cultured in vitro as free-floating spheres (neurospheres) in the presence of endothelium growth factor and/or basic fibroblast growth factor (Bonnamain et al, 2012).…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…To overcome these barriers, many researchers are exploring the clinical use of stem cells in gene therapies designed to treat cancer. Stem cells are capable of self-renewal, multilineage differentiation and inherent migration to tumor sites (19).…”
Section: Additional Effects Of Engineered Stem Cells Expressing a Thementioning
confidence: 99%
“…phenotype, reducing the likelihood for tumor growth. 83 NSCs have been shown to be an effective neural repair strategy in preclinical models of injury owing to their inherent ability to provide neuroprotection, decrease immunoreactivity, and secrete neurotrophic factors, such as glial-derived neurotrophic factor and brain-derived neurotrophic factor. 84 Previous work has also shown that NSCs can differentiate into dopaminergic-like cells, survive transplantation, integrate with the host architecture, and improve functional recovery.…”
Section: Regenerative Medicinementioning
confidence: 99%